Inefficiency and self-determination: Simulation-based evidence from Meiji Japan - Eric Weese; Masayoshi Hayashi; Masashi Nishikawa (Yale University, Economic Growth Center, 2015)
Does the exercise of the right of self-determination lead to inefficiency? This paper considers a set of centrally planned municipal mergers during the Meiji period, with data from Gifu prefecture. The observed merger pattern can be explained as a social optimum based on a very simple individual utility function. If individual villages had been allowed to choose their merger partners, counterfactual simulations show that the core is always non-empty, but core partitions contain about 80% more (postmerger) municipalities than the social optimum. Simulations are possible because core partitions can be calculated using repeated application of a mixed integer program.
Keywords: C63; C71; H77; K33; N95; 330; Municipal mergers; one-sided matching; moment inequalities; mixed integer programming; Gifu